Transport practices of Māori Kaumātua (Indigenous elders) in Aotearoa New Zealand: baseline findings from prospective older adults transport and health study (NZPATHS) - Sarah Colhoun; Rebecca McLean; Claire Cameron; Sue Crengle (BMC Public Health)
Abstract Background Transport is fundamental to support older Māori (kaumātua) wellbeing, facilitating ageing in place, social inclusion and access to cultural sites and practices – there is minimal research on transport practices of Indigenous populations and no published quantitative studies on the transport practices of kaumātua. Considering this data gap, we describe kaumātua transport practices and driving cessation planning in the context of a sample of older drivers from Aotearoa New Zealand. Methods Cross-sectional descriptive analysis of baseline data from New Zealand Prospective Older Adult Transport and Health Study (NZPATHS) of 1181 older drivers (65–96 years), 15% of whom identified as Māori. Data were gathered via computer assisted structured telephone interviews, including socio-demographic, health, transport and driving practice measures. Statistical tests performed were Mann Whitney, chi-square and Fisher’s exact tests, to provide contextual ethnic comparisons between categorical variables. Results Participants reported transport modes used in the previous three months. Similarly to non- Māori, kaumātua (driving at baseline) relied heavily on the private car for transport, as drivers (solely, 99%; or with passengers, 90%) and as passengers (87%). Compared to non-Māori, fewer Māori walked for transport (41% vs. 53%), and fewer used public transport (18% vs. 26%, bus/tram; 10% vs. 16%, train). Few kaumātua (4%) had made plans for not driving, a smaller proportion than for non-Māori (11%). Conclusions Kaumātua rely heavily on private cars for transport, yet when they can no longer drive, this dependence may present barriers to daily living and to maintaining cultural practices, health, and wellbeing. Increased transport infrastructure including public and community transport is needed to allow transport options beyond driving. Transport stakeholders must incorporate wider perspectives, including Indigenous peoples’ voices. This study provides data that can be used to inform and support improvements within the transport sector that reduce transport and health disadvantage and inequities.